Investigating overturning high sided vehicles through modeling high Reynolds number incompressible flow around a rectangular cylinder near a plane wall boundary - Sanchez, Daniel K., author; Venayagamoorthy, S. Karan, advisor; Chen, Suren, advisor; Olsen, Daniel, committee member (Colorado State University. Libraries, 2023)
Safety on public roadways is of paramount importance to road users, road authorities, the local economy, and the general wellbeing of society. High sided vehicles (commonly known as semitrucks in the United States (US) or lorries in the European Union (EU)) are used throughout the world for transporting freight, but they are susceptible to roll-over accidents due to high crosswind. The overturning of high sided vehicles is of concern during extreme wind events. In Boulder, Colorado, it is estimated that eight high wind events (with gusts greater than 75 mph) occur every year. The research field of overturning high sided vehicles is young compared to other areas of knowledge since CJ Baker of the United Kingdom (UK) opened the research field in 1986. The traditional method applied for evaluating the likelihood of a high sided vehicle to overturn is to use the predetermined rolling moment coefficient (Crolling) and translate the wind speed into a rolling moment. The resulting rolling moment can be compared to the restoring moment to determine the force required to overturn the high sided vehicle. This methodology requires that Crolling be accurate with respect to the high sided vehicle being analyzed. A recent study conglomerated many papers that have investigated Crolling, showing wide variation in the expected Crolling for yaw angles between 45° and 90° (a direct crosswind). Through this thesis, it was discovered that some of the variation is due to the fact that Crolling is Reynolds number dependent. In this thesis a comprehensive verification analysis and validation of a computational fluid dynamics (CFD) model was completed. Verification and validation are key components to performing a quality CFD analysis. When referring to verification, this traditionally implies a grid independence study to ensure the CFD results are accurate with respect to the mesh sizing. However, this study explores why a comprehensive verification study is necessary to evaluate the influence of the flow domain size for high Reynolds number incompressible flow around a bluff body. Additionally, it was found for flow around a rectangular cylinder near a plane wall boundary with a gap ratio of 0.407, that the drag coefficient (Cdrag) is dependent on Reynolds number. This fundamental field was connected to the application of overturning high sided vehicles, with the assumption that a 2D rectangular cylinder could represent the trailer section of a high sided vehicle. It was found that traditional studies on overturning high sided vehicles assume the aerodynamic coefficients are Reynolds number independent, whereas the fundamental field shows that there is a Reynolds number dependence. It is apparent that additional work on determining Crolling is needed due to the Reynolds number dependency.
Keywords: high Reynolds number; overturning; yaw; high sided vehicle; computational; rolling moment coefficient